Knowledge production and distribution by institutions of higher education in sub-Saharan Africa: Opportunities and challenges - Ondari-Okemwa, E (South African Journal of Higher Education, 2011)
This article focuses on available opportunities and challenges which institutions of higher education in sub-Saharan Africa face in producing and distributing knowledge. Institutions of higher education are also expected to produce knowledge workers for the knowledge economy. Knowledge production falls into Mode 1, in which problems are set and solved in a context governed by the largely academic interest of a specific community, and Mode 2, considered more socially accountable, accessible and reflexive. Knowledge produced by universities falls more into Mode 1. Objectives of the article are: to find out the potential role of sub-Saharan Africa-based institutions of higher education in producing and distributing knowledge; to explore ways of supplementing Mode 1 knowledge with Mode 2 knowledge, which has more social relevance; identify challenges faced by sub-Saharan Africa-based institutions of higher education in producing and distributing knowledge; find out how information technology may enhance knowledge production and distribution by institutions of higher education in sub-Saharan Africa; establish how the environments in which institutions of higher education in sub-Saharan Africa operate impact on knowledge production and distribution abilities of the institutions. A literature review was conducted to establish the state of knowledge production and distribution by institutions of higher education in sub-Saharan Africa. It was found out that institutions of higher education in sub-Saharan Africa face numerous challenges in producing knowledge. Challenges include poor infrastructure, declining budgetary allocations, brain drain and competition in knowledge production. Universities in sub-Saharan Africa can play a major role in producing knowledge and contributing to economic development in the region.